The Hamburg meteorite fall: Fireball trajectory, orbit, and dynamics. (11th August 2019) - Brown, P. G.; Vida, D.; Moser, D. E.; Granvik, M.; Koshak, W. J.; Chu, D.; Steckloff, J.; Licata, A.; Hariri, S.; Mason, J.; Mazur, M.; Cooke, W.; et al.
Abstract: The Hamburg (H4) meteorite fell on 17 January 2018 at 01:08 UT approximately 10 km north of Ann Arbor, Michigan. More than two dozen fragments totaling under 1 kg were recovered, primarily from frozen lake surfaces. The fireball initial velocity was 15.83 ± 0.05 km s −1, based on four independent records showing the fireball above 50 km altitude. The radiant had a zenith angle of 66.14 ± 0.29° and an azimuth of 121.56 ± 1.2°. The resulting low inclination (<1°) Apollo‐type orbit has a large aphelion distance and Tisserand value relative to Jupiter ( T j ) of 3. Two major flares dominate the energy deposition profile, centered at 24.1 and 21.7 km altitude, respectively, under dynamic pressures of 5–7 MPa. The Geostationary Lightning Mapper on the Geostationary Operational Environmental Satellite‐16 also detected the two main flares and their relative timing and peak flux agree with the video‐derived brightness profile. Our preferred total energy for the Hamburg fireball is 2–7 T TNT (8.4–28 × 10 9 J), which corresponds to a likely initial mass in the range of 60–225 kg or diameter between 0.3 and 0.5 m. Based on the model of Granvik et al. (2018), the meteorite originated in an escape route from the mid to outer asteroid belt. Hamburg is the 14th known H chondrite with an instrumentally derived preatmospheric orbit, half of which have small (<5°) inclinations making connection with (6) Hebe problematic. A definitive parent body consistent with all 14 known H chondrite orbits remains elusive.